Evaluation of Physical Stability of Phaleria Macrocarpa’s Leaf Extract Formulated in Nanoemulgel - Rosa Pratiwi; Anggun Feranisa; Elsa Yuliana Sukmawati (Denta Journal Kedokteran Gigi, 2023)
Background: Phaleria macrocarpa’s leaf contains alkaloids, saponins, phenols, tannins, and flavonoids which have antioxidant, anti-inflammatory, and antibacterial activities. The nanoemulgel preparation was chosen because it can penetrate well and quickly into the mucosa thereby increasing absorption. Physical stability tests need to be carried out to ensure the quality, safety and benefits of the gel meet the expected specifications and stable during storage. Objective: This study aims to determine which concentration has the most stable physical stability of pH and viscosity which were observed for 28 days. Materials and Methods: This was an experimental laboratory design, with 30 preparation divided into 3 groups, group of 30%, 40%, and 50% concentration preparation of nanoemulgel leaves of Phaleria macrocarpa. which were tested for pH tests and viscosity tests for 28 days which was observed every 7 days in climatic chamber. The pH and viscosity tests among groups were compared and analyzed by the Repeated Anova and Pos Hoc test. Results: Average pH test and viscosity test 30% concentration with the average baseline and h+28 pH values were 5,02 and 4,97 and the baseline and h+28 viscosity values were 1610 cPas and 1520 cPas. The results of the average concentration of 50% pH value at baseline = 4,65 and h+28 = 4,60. The mean baseline viscosity value=1290 cPas and h+28=1170 cPas. The results of the post-Wilcoxon test showed p>0.05 in the 30% concentration group for pH and viscosity tests showed that there was no significant difference in pH and viscosity values at a concentration of 30%, It means the pH value and viscosity of the 30% concentration preparation of nanoemulgel were relatively constant from baseline to h+28. Conclusion: It can be concluded that the pH and viscosity test of the preparation of nanoemulgel leaves of Phaleria macrocarpa at a concentration of 30% was the most stable pH and viscosity compared to concentrations of 40% and 50%.